Tinjauan Hybrid Contract Perspektif Maqashid Syari'ah - Agus Wahyu Irawan; Zulfatun Anisah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
The purpose of this study is to determine the hybrid or multi-contract contract pattern or perspective of al-ûuqûd al-murakkabah maqâshid syarîah. In the classical muamalah fiqh literature it is stated that a contract is prohibited because it contains gharar, but in its development, hybrid contracts in the contemporary muamalah fiqh literature are permitted but on condition that the contract that supports it is carried out independently. The acquisition of this hybrid contract is based on the principle of maslahah which is the core of the maqâshid syarî'ah. In Islamic banking financing, the majority built on hybrid contracts, of course, must conflict with regulations relating to the types of financing provided. This research is a normative legal research, using a conceptual approach. Because it is more focused on producing descriptive data from laws, books, books, and contract data (contracts) in sharia banking and maqâshid syarî'ah that underlie the emergence of fatwas or legal rules regarding the implementation of sharia banking products that contain hybrid contracts. The analysis technique used in this research is descriptive analysis. From the research conducted by the author, there are several maqâshid about the validity of the hybrid contract on Islamic banking that the author gets, namely: maintaining religion, soul, reason, religion, and property (halal oriented) Keyword : hybrid contract, and maqâshid syarî’ah.